2019
DOI: 10.1007/s11199-018-0992-7
|View full text |Cite
|
Sign up to set email alerts
|

Transnormativity and Transgender Identity Development: A Master Narrative Approach

Abstract: Despite rapidly shifting social dynamics and the recent increase in scholarship on transgender identity development, existing research on transgender identity has been theoretically isolated from the broader study of identity. This study involved a series of 4 qualitative focus groups (n = 15 participants), conducted in the United States, to identify master and alternative narratives guiding transgender identity development and explore the mechanisms by which transgender individuals navigate and negotiate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 60 publications
(73 reference statements)
4
90
0
1
Order By: Relevance
“…Halberstam, whom Wren cites, perhaps has some reasons to worry that gender variance can be prematurely stabilised into a fixed trans identity that casts their gender as ‘something clear and true’ (Wren, 2019). 9 Although the problem they describe pales in comparison to that of lack of support, it should be noted that many non-binary people who initially identified in a binary manner anecdotally report pressures to retain those initially expressed identities (Bradford & Syed, 2019). Many others report being forced into a certain relationship to their gender – I remember my mother telling me that I shouldn’t wear certain clothes ‘since I’m a woman now’ and have heard too many butch trans women lament the constant invalidation of their identities they face on the part of people who see themselves as supportive.…”
Section: Ethical Role Of Explorationmentioning
confidence: 99%
“…Halberstam, whom Wren cites, perhaps has some reasons to worry that gender variance can be prematurely stabilised into a fixed trans identity that casts their gender as ‘something clear and true’ (Wren, 2019). 9 Although the problem they describe pales in comparison to that of lack of support, it should be noted that many non-binary people who initially identified in a binary manner anecdotally report pressures to retain those initially expressed identities (Bradford & Syed, 2019). Many others report being forced into a certain relationship to their gender – I remember my mother telling me that I shouldn’t wear certain clothes ‘since I’m a woman now’ and have heard too many butch trans women lament the constant invalidation of their identities they face on the part of people who see themselves as supportive.…”
Section: Ethical Role Of Explorationmentioning
confidence: 99%
“…Using a grounded theory approach with general questions focused on the dynamic relationship between internal identity, presentation of self, and external validation, interviews with 18 transgender and gender nonconforming (GNC) individuals revealed a deeply felt need to present and receive acknowledgment (verification) and behavioral affirmation (validation) in ways that attested to their internal gender identity. While trans identity development and affirmation models have acknowledged the importance of these constructs, research has been slow to study the specific elements of identity development surrounding social and interpersonal negotiations and their role in the self-verification process (Bradford & Syed, 2019;Mullen & Moane, 2013;Webster, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Williams (2018) suggested that additions such as Bussey's (2011) previously mentioned perspective, that gender identity includes a multiplicity of factors, could be used to augment the study of gender identity development by recognizing the involvement of personal exploration and its linkage with social climates and interpersonal interactions in the identity process. There has been consensus, however, among gender identity researchers (Bradford & Syed, 2019;Mullen & Moane, 2013;Webster, 2019) that the social and interpersonal aspects of identity development, specifically the effect of one's interactions and relationships with others, have been shortchanged in trans identity research. Rectifying this would require a general alliance between transgender identity research and broader identity theories, as well as the inclusion of studies devoted to transgender identity within larger identity models, a focus that has been all but missing from past and present identity theories (Bradford & Syed, 2019).…”
Section: Trans Identity Development Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…People of all gender identities can be prone to transnormative assumptions because transnormativity operates as a "regulatory normative ideology," which can be understood as an organizing principle that supports systemic structures of power within Western society (Johnson, 2016, p. 466). Some examples of transnormative assumptions include expecting anybody who is not cisgender to medically transition and/or expecting that all transgender and nonbinary people 'realized' they were not cisgender in childhood Bradford & Syed, 2019). Transnormative assumptions also suggest that all transgender and nonbinary people have to conform to transnormativity in order to move the transgender rights movement forward-a notion that is further based on the idea that transgender people need to medically transition in order to be socially recognized as having a binary gender identity (i.e., woman or man; Bradford & Syed, 2019).…”
Section: Transnormative Assumptionsmentioning
confidence: 99%